(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The annotated list of vascular plants of the seaside-steppe part of the Northern Pryazov’ya (which a former Berdyansk military training area and is valuable from the botanical point of view) is presented. It still has fragments of native grass-fescue-feather grass steppes of Festuco-Brometea Br.-Bl. et R.Tx. in Br.-Bl. 1949 class. Flora of the steppe area, which is about 3,000 hectares has 531 species of vascular plants, that is about 34% of the flora of Zaporozhye region. On this site 38 rare plant species grow, three of which have international protection status, 7 has national, and 28 has regional status. Taking into account floristic and phytocoenotic diversity, it is proposed to create a national botanical reserve «Berdyansk steppe» on part of this area.